Global sensitivity analysis of the deformation behavior of sluice chamber structure. (December 2021) - Liang, Jiaming; Li, Zhanchao; Ji, Qingfeng; Lu, Weigang; Cao, Qiulin; Ahmed, Eladly
Abstract: The engineering of sluice has many functions, such as flood control, irrigation, navigation, and power generation. The safety of sluice structure is the premise of its functions and benefits. Moreover, the deformation behavior of the sluice chamber is closely related to the safe operation of the sluice. Firstly, existing literature on sluice research using FEM is investigated and analyzed to determine the calculation model and influencing factors. Secondly, the global sensitivity analysis method of the sluice chamber is constructed based on the Sobol sequence random sampling method and the global sensitivity analysis method based on variance. Finally, according to the distribution rule of the first-order and total-order sensitivity coefficients in the sluice chamber, the typical locations are determined, and the linear and nonlinear relations between the main influencing factors and the deformation indexes of each location are analyzed. An example shows that the deformation of the sluice chamber is mainly settlement, and the major factor is the deformation modulus of foundation soil. Each index model of sluice deformation can be considered as additive. The research results have significant reference value for clarifying the influence mechanism of the sluice chamber deformation behavior and improving the design, operation management, and safety evaluation of sluice structure.